ASP.NET Core - SOLID and Clean Architecture (.NET 5 and up) - Williams, Trevoir (Packt Publishing, 2021)
Create a SOLID and testable ASP.NET Core application using the best industry standards and clean architecture About This Video Build a strong foundation in .NET 5 Clean Architecture Use advanced tools such as MediatR, Automapper, Fluent API, and Validation Use Identity and JWT to secure application API In Detail Creating a modular, testable, and maintainable application in .NET Core requires a solid foundation. Setting up an application architecture requires foresight and much consideration as early decisions will impact how easily the application is extended and maintained. In the long run though, applications need to be maintained and, in this case, extended. Between its design and the way the code was written, neither is really possible and so the application needs to be redesigned and future-proofed. In this course, we will explore foundational architectural principles that help with the creation of maintainable code. Next, discover how to set up a real-world application architecture with ASP.NET Core. Then, you will learn how to plug in different, common blocks such as email and authentication and have a foundation to plug in other third-party services as needed. By the end of this course, you will have the skills and knowledge of creating a testable and maintainable ASP.NET Core application needed to architect real-world enterprise .NET Core apps. Who this book is for To take this course, you will need to have some knowledge of .NET Core development and C#. Late beginner to intermediate programmers can benefit from this course.
Online resource; Title from title screen (viewed September 28, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos